Comprehensive Mental Health Care: The Complementary Role of the Family Doctor and the Psychologist in Early Detection - Marquez, Luis Eduardo Sevilla; Canto, Berenice Morales; Lara, Sergio Manuel Montes (Journal of Posthumanism, 2025)
Mental health has become a priority in primary care systems, especially after the increase in disorders such as anxiety and depression in post-pandemic contexts. This article explores the complementary role of the family physician and the psychologist in the early detection of mental health problems. Interdisciplinary integration is proposed as an effective strategy to address timely care, improve clinical outcomes and optimize health resources. The study was developed through a systematic literature review and interviews with health professionals. The results highlight that interprofessional collaboration strengthens the early identification of symptoms, increases adherence to treatment and reduces stigmatization. It is concluded that comprehensive and interdisciplinary care is crucial to respond to the current challenges of mental health in primary care.